Achiasmatic meiosis in the unisexual Amazon molly, Poecilia formosa - Dedukh, Dmitrij; da Cruz, Irene; Kneitz, Susanne; Marta, Anatolie; Ormanns, Jenny; Tichopád, Tomáš; Lu, Yuan; Alsheimer, Manfred; Janko, Karel; Schartl, Manfred (Chromosome research, 2022)
Unisexual reproduction, which generates clonal offspring, is an alternative strategy to sexual breeding and occurs even in vertebrates. A wide range of non-sexual reproductive modes have been described, and one of the least understood questions is how such pathways emerged and how they mechanistically proceed. The Amazon molly, Poecilia formosa, needs sperm from males of related species to trigger the parthenogenetic development of diploid eggs. However, the mechanism, of how the unreduced female gametes are produced, remains unclear. Cytological analyses revealed that the chromosomes of primary oocytes initiate pachytene but do not proceed to bivalent formation and meiotic crossovers. Comparing ovary transcriptomes of P. formosa and its sexual parental species revealed expression levels of meiosis-specific genes deviating from P. mexicana but not from P. latipinna. Furthermore, several meiosis genes show biased expression towards one of the two alleles from the parental genomes. We infer from our data that in the Amazon molly diploid oocytes are generated by apomixis due to a failure in the synapsis of homologous chromosomes. The fact that this failure is not reflected in the differential expression of known meiosis genes suggests the underlying molecular mechanism may be dysregulation on the protein level or misexpression of a so far unknown meiosis gene, and/or hybrid dysgenesis because of compromised interaction of proteins from diverged genomes.
Keywords: sperma; Female; Meiosis; zvířata; Poecilia; Synaptonemal complex; meióza; ženské pohlaví; Recombination; Male; Achiasmatic; transkriptom; Semen; Transcriptome; Animals; mužské pohlaví; Taiwan; Crossing-over; živorodka; Parthenogenesis; Oogenesis